Multiple first-line therapeutic strategies to mitigate artemisinin resistance: cost analysis of a pilot study from a health system perspective in Kaya health district, Burkina Faso - Rosemonde M. Guissou; Jean Moïse T. Kaboré; Issiaka Soulama; Denise Hien; Yacouba Nombré; Alfred B. Tiono; Christian Burri; Sodiomon B. Sirima (Malaria Journal)
Abstract Background The emergence of artemisinin resistance in Africa is an increasingly evident threat to malaria control and elimination, and anticipatory measures are needed. Mathematical modelling studies demonstrated that the simultaneous deployment of multiple first-line therapy (MFT) strategies delays the spread of resistance, but there is no evidence concerning the implementation of these strategies, which is an important factor in decision-making. Incremental financial costs of implementing a MFT strategy at a district scale were estimated, analysed and compared to routine practice, with a scaling-up perspective by the government. Then, implications of the findings for improving malaria control in Burkina Faso and other parts of sub-Saharan Africa were highlighted. Methods Microcosting and activity-based costing approaches were used to assess the cost for providers, of the MFT pilot study implemented in Kaya Heath District, from December 2019 to November 2020. Quantitative et qualitative data were collected through seven semi-structured and thirty-eight structured interviews. The interviews were conducted with research team (including a member of the National Malaria Control Programme), the health district officials (chief doctor and chief pharmacist) and with the managers of the public health facilities where the MFT strategy was implemented. Results Of the six activities involved in routine malaria care delivery, four incur additional costs when the MFT strategy is implemented: support material production, health worker training and supervision, and the chosen artemisinin-based combination therapy (ACT) costs, if different from the standard cost. On the basis of uncomplicated malaria cases reported at the national level in 2022, MFT implementation costs at the country level were estimated at 20,840,880 USD, of which 92% were related to drug costs with a recurrent character. The weight of drug costs in the MFT strategy depends on the artemisinin-based combination chosen and on subsidies and free care policies. In the pilot strategy, the cost of MFT drugs was more than double that under routine practice: 19,175,568 USD versus 8,554,365 USD. Conclusion The results of the MFT strategy cost analysis presented here may assist policy makers in their choice of malaria ACT combinations for mitigating the emergence of drug resistance. Although the MFT strategy costs almost twice as much as the current single first-line treatment strategy cost savings due to avoiding treatment failure are likely to be substantial. The results also highlight the necessity of better organizing and stabilizing malaria control financing sources particularly in view of the recent funding challenges facing the global health system.